THE DEVELOPMENT OF NATIONAL MATHEMATICS EDUCATION AT THE TURN OF THE MILLENIUM - Rudenko, Nina M. (Educological discourse, 2016)
In the article the notion of national mathematicsis analyzed; the contribution to the mathematics of Ukrainian academician A. Samoilenko, doctor of physical and mathematical sciences is considered.